Justice Connectivity in the Criminal Prosecution of Human Trafficking - Saimima, Ika Dewi Sartika; Sanaky, Mochammad Syafruddin Rezky (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The involvement of members of the army of the Republic of Indonesia and The Police of the Republic of Indonesia became a special obstacle in the handling of human trafficking cases. The difficulties are due to the existence of special regulations governing the courts applicable to members of the Indonesian army who commit criminal acts.Purposes of the Research: The case may be dealt with in conjunction with a criminal offense of trafficking in persons, given that the offense has fulfilled the element of involvement (also, deelneming) or jointly (mede dader) between a civilian and a person with military status in the criminal offense of trafficking.Methods of the Research: The research used normative jurisprudence, focusing on primary legal material such as Act No. 21 of 2007 on Punishment of Trafficking in Persons, Law No. 31 of 1997 on Military Justice, and Law No. 2 of 2002 on the State Police of the Republic of Indonesia. The research was descriptive-analytical, interpreting the law according to its context and analyzing its results in a qualitative, descriptive manner. Secondary legal material included publications on human rights protection, particularly those relating to women and children. The fact approach was used to study human trafficking facts and provide critical analysis. Library documents, books, and journals were also analyzed. Data analysis involved document study techniques and qualitative analysis, with the results and author's analysis of relevant theories.Results of the Research: The article addresses the Indonesian Army and Police's involvement in human trafficking offenses, emphasizing the intricacies and problems of prosecuting such instances. The author believes that the judicial system must promote justice and openness in such circumstances. The Indonesian legal system recognizes both military and civilian jurisdiction over crimes committed by military personnel, but implementation gaps cause uncertainty and delays in judicial processes. Handling crimes involving several institutions necessitates close teamwork, particularly among the Indonesian army and police. The mechanism to facilitate collaborative processing of human trafficking cases is connectedness justice, which decides which court has the authority to punish members of the Indonesian army for human trafficking.